An electrokinetic study of synthetic greigite and pyrrhotite - Dekkers, M.J.; Schoonen, M.A.A. (Elsevier, 1994)
The isoefectric points of synthetic greigite, Fe&, and pyrrhotite, Fe, _& in 10 -3- 1.1 10 -* M NaCl solution at or, < lop4 and as < 10W4 were determined to be pH 3 and 2, respectively. Below pH 2 for pyrrhotite and below pH 3 for greigite, the surfaces are positively charged; above these pH values the surfaces are negatively charged. Upon addition of sulfidic sulfur (H$, HS-), traces of terrestrial humic acids, or a combination of sulfidic sulfur and terrestrial humic acids, the surfaces are negatively charged over the entire pH range (2-11) studied. Because humic acid and sulfidic sulfur influence the zeta potential of the iron sulfide surfaces, they must he adsorbed within the shear plane of the double layer, close to the actual surface of the minerals. The isoelectric points for greigite and pyrrhotite in the absence of either sulfidic sulfur or humic acid are very close to those for natural pyrite (Fe&) and sphalerite (ZnS), as well as synthetic ZnS, CuS, CdS, galena (PbS), chalcopyrite (CuFeSa), and elemental sulfur. It is plausible that the speciation of thiol surface groups (ES-H i, ~--II*, =S- -) dominates the surface charge on all these phases. The increase in net zeta potential upon the addition of sulfidic sulfur is, however, not well understood.
Keywords: Aardwetenschappen